Improving Students’ Vocabulary Achievement Through Word Walls Strategy - Decy Anggriani; Sumarsih - (Universitas Negeri Medan, 2013)
ABSTRACTThis study aims at finding out whether the application of Word Walls strategy significantly improves the students’ vocabulary achievement. This study was conducted by using classroom action research. The subject of the research was VII-5 class SMP Negeri 1 Pagar Merbau which consisted of 25 students. The research was conducted in two cycles and each cycle consisted of three meetings. The result showed that the improvement of the students’ scores from the first test in orientation test to the third test in cycle-II test. In the first test in orientation test, the mean was 48.48, in the second test in cycle-I test, the mean was 63.68, and the third test in cycle-II test, it was improved to be 79.04. Based on the diary notes, observation sheet, and questionnaire, it was found that the teaching learning activities ran well. Students were active and enthusiastic during the teaching learning process in the second cycle than the first one. The result of the researcher showed that the use of word walls strategy significantly improved students’ vocabulary.Keywords: Vocabulary, Action Research, Word Walls Strategy,